Kindness, Politics, and Religion: An Interview with Naomi Shihab Nye. (25th April 2019) - Corrigan, Paul T
Abstract: In this interview, Naomi Shihab Nye gives her most sustained comments to date on the religious and spiritual sensibility in her work. She shares about growing up in an interreligious environment and majoring in world religions in college, she critiques the way religion is often used for power and control, and she discusses the importance for her of practicing contemplation and respecting the mysteries of the world. She describes why she likes the word "tend" so much and how war erases "everything that's been tended." She also discusses a number of specific works she's written that engage spiritual or religious themes (such as God, prayer, empathy), including her famous poem "Kindness" (1980), which came to her all at once in something like a spiritual experience.